Tatalaksana Anestesi pada Pasien Cedera Otak Traumatik Berat - Rani Tiara; Bambang Eko Subekti (Medula, 2020)
Anesthetic management in 40-year-old men, body weight 60 kg, height 172 cm. Patient brought to the emergency department due to a traffic accident, fell from a motorcycle. In the emergency department, initial management was management by evaluating the clear airway, breathing with breath rate 20-24x /min, and circulation with blood pressure 90/60 mmHg and pulse rate 64x /min, with patient GCS E3V1M3. Patients diagnosed with intracerebral hemorrhage and subdural hemorrhage who need perform hematoma evacuation with craniotomy procedure, with ASA III in patient physical status. Surgery is performed under general anesthesia, with the specific procedure remaining to stable and maintaining intracranial pressure in optimal condition. Hemodynamics stabilitations by maintaining MAP 70-100 mmHg. The operation held for 2.5 hours, after the operation, the patient was moved to the recovery room and received for further treatment in the surgical care room. Faster management of head injuries, resuscitation with cerebral protection and management of intensive therapy can improve the outcome of patients.